(Pro)renin Receptor Inhibition Reprograms Hepatic Lipid Metabolism and Protects Mice From Diet-Induced Obesity and Hepatosteatosis. Issue 5 (2nd March 2018) - Ren, Liwei; Sun, Yuan; Lu, Hong; Ye, Dien; Han, Lijuan; Wang, Na; Daugherty, Alan; Li, Furong; Wang, Miaomiao; Su, Fengting; Tao, Wenjun; Sun, Jie; et al.
Abstract : Rationale: : An elevated level of plasma LDL (low-density lipoprotein) is an established risk factor for cardiovascular disease. Recently, we reported that the (pro)renin receptor ([P]RR) regulates LDL metabolism in vitro via the LDLR (LDL receptor) and SORT1 (sortilin-1), independently of the renin–angiotensin system. Objectives: : To investigate the physiological role of (P)RR in lipid metabolism in vivo. Methods and Results: : We used N-acetylgalactosamine modified antisense oligonucleotides to specifically inhibit hepatic (P)RR expression in C57BL/6 mice and studied the consequences this has on lipid metabolism. In line with our earlier report, hepatic (P)RR silencing increased plasma LDL-C (LDL cholesterol). Unexpectedly, this also resulted in markedly reduced plasma triglycerides in a SORT1-independent manner in C57BL/6 mice fed a normal- or high-fat diet. In LDLR-deficient mice, hepatic (P)RR inhibition reduced both plasma cholesterol and triglycerides, in a diet-independent manner. Mechanistically, we found that (P)RR inhibition decreased protein abundance of ACC (acetyl-CoA carboxylase) and PDH (pyruvate dehydrogenase). This alteration reprograms hepatic metabolism, leading to reduced lipid synthesis and increased fatty acid oxidation. As a result, hepatic (P)RR inhibition attenuated diet-induced obesity and hepatosteatosis. Conclusions: : Collectively, our study suggests that (P)RR plays a key role in energy homeostasis and regulation of plasma lipids by integrating hepatic glucose and lipid metabolism. Abstract : Supplemental Digital Content is available in the text.